Корупційні ризики в тендерній політиці підприємства - Никоненко, Андрій Володимирович (My University, 2020)
Розглянуто сутність публічних закупівель, ризики підприємства в сфері публічних закупівель, втрати держави від корупції в сфері публічних закупівель, методи корупційних порушень в ході публічних закупівель, недоліки вітчизняної системи публічних закупівель. The essence of public procurement, the risks of an enterprise when participating in public procurement, losses of the state from corruption in the field of public procurement, methods of corruption violations in the course of public procurement, shortcomings of the domestic public procurement syste are considered
Keywords: кафедра маркетингу; тендерна політика підприємства; публічні закупівлі; корупція; tender policy of the enterprise; public procurement; corruption